An analysis of the factors influencing the selection of a given form of learning - Elzbieta Macioszek; Agata Kurek (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
In modern times, we observe many new trends, including technological, economic, cultural, ecological, and economic changes, which are part of the fast and uneven process of globalization. The current educational system is undergoing global changes caused by the current situation related to the COVID-19 pandemic, forcing both academic teachers and students not only to change the way they function or operate, but also to change attitudes and beliefs, especially regarding new media and remote learning. The article presents an analysis of the factors influencing the selection of a given form of learning in technical faculties from among three hypothetical options: stationary learning, remote learning, and hybrid learning. This analysis was based on the results of a survey conducted among students after two years of experience studying in the COVID-19 pandemic. The obtained results allowed for the selection of features influencing the choice of a given form of learning by the students. The knowledge of these factors is especially valuable for university authorities making decisions about the form of student learning after the end of the COVID-19 pandemic.
Keywords: 650; remote learning; survey-based analysis; innovation in learning